Editorial (Inglês) - Mota, Mauricio (REVISTA QUAESTIO IURIS, 2018)
The Journal Quaestio Iuris, indexed in the Web of Science, on a quarterly basis, in this volume 11, issue 04, 2018, is pleased to inform all its readers that it has been ranked among the best-evaluated foreign journals of Scholarly Publishers Indicators in Humanities and Social Sciences, Spain, with ICEE of 8,000. Scholarly Publishers Indicators (SPI) is an information system that provides indicators and tools related to publishers, journals or research interests in the humanities and social sciences. In its origin, it was created as one of the results of the research project "Categorization of scientific publications in Human and Social Sciences", funded by CSIC. Now, thanks to the research developed in the project of the National R & D & I Plan, "Evaluation of scientific publishers (Spanish and foreign) of books in Human and Social Sciences through expert opinion and analysis of editorial processes ", Spain, the system can grow. The indicators that are included in the SPI are intended as a reference in the processes of evaluation of scientific journals and allow the objectification of some concepts such as the prestige of the scientific journal. In this issue of the Journal we have kept our staff of our reviewers / evaluators, from countless states of the country and foreign teachers, in a total of more than 650 (six hundred and fifty) evaluators. We also publish, for the immediate consultation of the readers, the links to the various national and international indexes of journals and periodicals where our Journal Quaestio Iuris is indexed. We thank, as always, all the readers, authors, evaluators and collaborators for the collaboration and trust and for the always excellent work done. We always remember that submissions to the Journal are permanent and must be carried out by the system, directly on the Journal’s page.